Nilai-nilai Pendidikan Karakter dalam Novel The Lost Symbol Karya Dan Brown - Karmila (Indonesian Journal of Applied Linguistics Review, 2017)
This study aims to gain an understanding of The Lost Symbol novel by Dan brown focuses on the values of character education as motivation to be a man of noble. The values of character education is analyzed using semiotic structuralism, aims to determine the meaning and signs contained in The Lost Symbol novel. The method used is qualitative research by interpreting the words in the form of dialogues, expressions and body gestures of the characters in the story. Data used in the form of text that describes the content of the values of character education through a document form of The Lost Symbol novel by Dan Brown. The novel describes how to establish a true frienship, the teacher as hero inchanging times, and the role of parents in instiling positive character in children early. This study found the values of character education obtained in each chapter. The values of character education in The Lost Symbol novel included the values of character education in relation to God, the values of character education in relation to ourselves, the values of character education in relation to others, the values of character in relation to the environment, and the values of nationality